2008
DOI: 10.1007/s11284-008-0471-7
|View full text |Cite
|
Sign up to set email alerts
|

Detritivory: stoichiometry of a neglected trophic level

Abstract: Previous syntheses have identified the key roles that phylogeny, body size, and trophic level play in determining arthropod stoichiometry. To date, however, detritivores have been largely omitted from such syntheses, despite their importance in nutrient cycling, biodiversity, and food web interactions. Here, we report on a compiled database of the allometry and nutritional stoichiometry (N and P) of detritivorous arthropods. Overall, both N and P content for detritivores varied among major phylogenetic lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 37 publications
8
98
1
Order By: Relevance
“…While P concentration differs markedly between autotrophic and heterotrophic organisms (Fanin et al 2013), it does not show considerable changes between insect consumers of different trophic levels (Woods et al 2004;Martinson et al 2008). In order to assess multitrophic responses to differing resource stoichiometry, we therefore focused on C∶N ratios, since N concentration differs both between autotrophs and heterotrophs (Fanin et al 2013) and between consumers of different trophic levels (Fagan et al 2002).…”
Section: Stoichiometric Analyses Of Animal and Leaf-litter Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…While P concentration differs markedly between autotrophic and heterotrophic organisms (Fanin et al 2013), it does not show considerable changes between insect consumers of different trophic levels (Woods et al 2004;Martinson et al 2008). In order to assess multitrophic responses to differing resource stoichiometry, we therefore focused on C∶N ratios, since N concentration differs both between autotrophs and heterotrophs (Fanin et al 2013) and between consumers of different trophic levels (Fagan et al 2002).…”
Section: Stoichiometric Analyses Of Animal and Leaf-litter Samplesmentioning
confidence: 99%
“…However, with better resolved trophic structure of these communities, investigating how relative amounts of N, P, Na, and Ca vary along the food chain (Martinson et al 2008) and differently alter consumer responses to resource depletion across trophic levels seems promising. Furthermore, investigating the effects of variation in other elements on consumer diversity and feeding rates across trophic levels will be a future challenge to unravel new patterns in community structure.…”
Section: Future Directionsmentioning
confidence: 99%
“…With respect to zooplankton-C composition, our δ 13 C results were relatively surprising because several studies have shown that bacterial growth based on humic DOC may contribute significantly to zooplankton diet and growth (Karlsson et al, 2003, Daniel et al, 2005, and zooplankton may directly consume terrestrial POC (Cole et al, 2006). Stoichiometric imbalances between detritivores and herbivores in relation to primary producers are a widespread pattern in aquatic and terrestrial ecosystems (Martinson et al, 2008). These imbalances can explain the N and P depletion in sediments when compared to the composition of aquatic macrophyte tissues and the almost absolute predominance of phytoplankton C in zooplankton tissues.…”
Section: Discussionmentioning
confidence: 72%
“…This suggests a coupling between the absorption of these nutrients by decomposers or an N and P link to a C-rich structure that is resistent to decompose. Them both appear to be the case in E. interstincta stands once it have high N:P ratios, which are limiting nutrients to decomposers (Martinson et al, 2008), and have the highest cellwall fraction according to Suhett (2007). Weak correlations between C and N and a low C:N ratio suggest an enhancement of the influence of had a high C:nutrient ratios.…”
Section: Discussionmentioning
confidence: 95%
“…For example, the oxygen content (O) of organisms may be a signature of their physiological conditions and of the type of molecules they store (Fagerbakke et al, 1996; Table 1; see also Han et al, 2011). Biases in the groups of organisms represented in datasets also exist, with unicellular algae, terrestrial vascular plants, crustacean zooplankton-mostly herbivorous-and insects overrepresented (but see Amatangelo and Vitousek, 2008;Martinson et al, 2008;Xia et al, 2014;Danger et al, 2016 for examples of recent attempts at evening the balance).…”
Section: Organismmentioning
confidence: 99%